2001
DOI: 10.1177/001440290106800107
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Odds: Qualitative Examination of Resilience among Formerly Incarcerated Adolescents

Abstract: Adolescents who have been incarcerated are at extreme risk for poor adult outcomes. However, some former youth offenders become successful, happy adults, presenting a profile of strength and coping known as resilience. This article describes the results of a 5-year qualitative examination of resilience among a group of adolescents transitioning from youth correctional facilities back into their communities. Topics discussed include predelinquent histories, experiences in the correctional system, and postcorrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 13 publications
7
70
0
7
Order By: Relevance
“…Since our measures of the interventions were the engagement rates of activities in which the transition specialist supported the youth's engagement, we may need to look further for how to explore the influence of the transition specialist's interaction with the youth. Research on resilience of youth involved in the juvenile justice system pointed to the importance of a mentoring type of relationship needed for these youth (Todis et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Since our measures of the interventions were the engagement rates of activities in which the transition specialist supported the youth's engagement, we may need to look further for how to explore the influence of the transition specialist's interaction with the youth. Research on resilience of youth involved in the juvenile justice system pointed to the importance of a mentoring type of relationship needed for these youth (Todis et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Children first navigate their way to health resources, either by purposefully seeking out what they need physically, psychologically, socially and spiritually, or as is just as often the case, allowing life to serendipitously present opportunities through chance encounters (Ungar, 2004). A number of qualitative studies have shown that at-risk children manipulate service providers to some degree in order to create opportunities to access the health resources that sustain wellbeing (de Antoni & Koller, 2000;Felsman, 1989;Hauser, 1999;Klevens & Roca, 1999;Todis, Bullis, Waintrup, Schultz & d'Ambrosio, 2001;Tyler, Tyler, Tommasello, & Connolly, 1992;Schofield, 2000;Rak, 2002;Ungar, 2001;Ungar, Teram, & Picketts, 2001). Having successfully navigated their way into the role as client/resident/patient/student of one system or the other, children argue they then become actively engaged in negotiating with service providers for the health resources that fit best for them.…”
Section: Navigation and Negotiationmentioning
confidence: 99%
“…In a five year qualitative study of resilience, youth were identified as at-risk because of their involvement in antisocial behaviour which led to a subsequent incarceration (Todis, Bullis, Waintrup, Schultz & D'Ambrosio, 2001). The study was conducted over a five-year period as 15 youth who were identified as potentially resilient by their correction officers transitioned from a group home to independent living.…”
Section: Riskmentioning
confidence: 99%